E Increasing Artificial Intelligence Literacy for Information Systems Students thru Educational Workshops at Kalla Institute - Andi Hutami Endang; Andi Jamiati Paramita; Abdul Hakim; Hany Alexandra; Yabes Dwinugroho; Furqan Zakiyabarsi; Anhar Januar Malik (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The rapid development of Artificial Intelligence (AI) is creating a gap between conventional curricula and the industry's need for AI literacy among students of Information Systems. Information Systems (IS) students, as future designers and developers of technology, play a crucial role in understanding and applying AI effectively and ethically. This community service activity aims to enhance the understanding of IS students at Kalla Institute regarding the concepts, trends, benefits, challenges, and ethical implications of the AI revolution in education. This service was realized through an internal workshop delivered directly by a lecturer from the Information Systems Study Program at Kalla Institute. The implementation method involved interactive lectures, discussions, and question-and-answer sessions that explored various aspects of AI in the educational context, ranging from basic concepts and practical applications to ethical considerations. Activity evaluation was conducted through pre-test and post-test questionnaires, as well as qualitative feedback, to measure the increase in participants' understanding and perceptions. The results showed a significant increase in understanding among student participants regarding the role and impact of AI in education, as well as high enthusiasm for utilizing AI for learning and future career development. This service activity successfully increased the understanding and readiness of Kalla Institute students to apply AI ethically and responsibly, contributing to the achievement of the institution's vision.